Melyna: innovative facial serum / Mohamed Syazwan Osman ... [et al.] - Osman, Mohamed Syazwan; Salim, Nur Syifa; Azis, Najwa; Zaini, Nur Aqilah (Universiti Teknologi MARA, Kedah, 2019)
Apparently, skin is one of the important tissues to human being that protect us from external contamination. As results, skins are typically highly sensitive to any changes to environmental surroundings. Hence, tendency for human to be contaminated with germs, dust and others is tremendous and potential health issues such as rashness, dermatitis etc is highly anticipated. Various efforts have been made to combat this issue with the introduction of drugs in the shape of cream in the market. Nonetheless, readily available products are deemed costly and susceptible from unwarranted adverse health effects. Recently, there is an enormous demand to go back to nature to sought complimentary and medicinal plants to combat this issue. Not only there are more affordable and less stringent regulatory roadblocks, this alternative medicine possesses significant medicinal benefits that react in symbiosis to each other’s in natural way. Herein, we propose an innovation called Melyna: Innovative facial serum derived from Beijing grass extract (Murdania bracteata) as main active ingredients. Various study and researches have shown that Beijing grass extract has exhibited antioxidant, anti-inflammatory, exfoliation of dead cells and other nutritional benefits. Studies have also shown that beijing grass extract is relatively not toxic to humans.. Thus, with novel formulation, BRostro might enhance and improve skin qualities and overall comfort and quality health skin experiences to consumers.